Effect of environment on cyclic fatigue of ProTaper Next rotary files - Tariq S Abuhaimed (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of the study was to evaluate the effect of different irrigation solutions on cyclic fatigue of ProTaper Next (PTN) rotary files. Materials and Methods: A total of 50 files were divided into 5 groups according to the environment in which cyclic fatigue test was carried out as follows: chlorhexidine (CHX) 2%, ethylenediaminetetraacetic acid 17%, saline, sodium hypochlorite 6%, and air (control group). A specially designed testing device was assembled utilizing an artificial canal made of a heat-resistant glass tube. The tube had a 1.2 mm diameter, an angle of curvature of 60°, and a radius of curvature 6 mm. Before each fatigue test, the tube was filled with fresh irrigation solution except air group, which was left dry. The mean number of cycles to failure was counted then fractography and length of broken segment were analyzed after failure. Statistical analyses were performed using one-way ANOVA test. Results: The CHX group was the most resistant to cyclic fatigue compared to all groups (P < 0.05). No significant difference was found between all other solutions or dry group (P > 0.05). Fractographic analysis of all groups showed signs of a fatigue failure. A crack site was seen followed by a striation area leading to a dimples overload area. The length of broken segments was not significantly different among all groups (P = 0.37). Conclusion: Although liquid media may function as lubrication, all irrigants except CHX failed to increase the fatigue life of PTN files when compared to dry conditions.